Non-Standard Eggs as an Alternative Source of Protein - Nazirova Raxnamoxon Muxtorovna; Ahmedova Ziyoda (Web of Journals Publishing, 2023)
It is known that eggs are a complete food product. Eggs contain a full range of essential amino acids necessary for the full functioning of the body. The article discusses the problem of using broken eggs in the production of feed for young animals of various farm animals
Keywords: protein, eggs, proteins, atomization, egg powder, digestibility, phospholipids, protein source.